Recall that the equation of a line that passes through two points is given by the following formula:
![y-y_1=(y_2-y_1)/(x_2-x_1)(x-x_1).](https://img.qammunity.org/2023/formulas/mathematics/college/173ncqk8d261fdp7khmyauyxyn5plaktev.png)
Notice that the above formula gives us the equation of the line in point-slope form. Substituting the given values in the above formula, we get:
![y-(-1)=(-1-4)/(2-8)(x-2).](https://img.qammunity.org/2023/formulas/mathematics/high-school/1kmpleh95nnb5nfw9lhmq3507isw1ckcnr.png)
Simplifying the above result, we get:
![y+1=(5)/(6)(x-2).](https://img.qammunity.org/2023/formulas/mathematics/high-school/z5dcba59nnwzcbb6grpfujredig4u5xnbd.png)
Now, taking the above equation to its standard form, we get:
![\begin{gathered} 6y+6=5(x-2), \\ 6y+6=5x-10, \\ 6y-5x=-10-6, \\ -5x+6y=-16. \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/d8l6gom7bqvyqjk2ezv4w7g6qv9t3ps3nn.png)
Answer:
![y+1=(5)/(6)(x-2);-5x+6y=-16.](https://img.qammunity.org/2023/formulas/mathematics/high-school/i8s2ti72vj4beupb5yiqey6k3ml3vudo8k.png)